2020
DOI: 10.2169/internalmedicine.4447-20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Esophageal Eosinophilia According to Endoscopic Phenotypes

Abstract: Objective Esophageal eosinophilia (EE), a histological hallmark of eosinophilic esophagitis, is classified into two endoscopic phenotypes: localized and diffuse EE. Our aim was to determine the prevalence of EE localized in the lower esophagus and to describe its clinical features in comparison with diffuse EE. Methods Data from 81 consecutive patients with EE were retrospectively investigated. EE was histologically defined as ≥15 eosinophils per high-power field. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The inflammatory and fibrostenotic scores were calculated ( 10 ). Regarding the location of endoscopic findings, the phenotype was divided into diffuse and localized EE in the previous study ( 11 ). The localized type was defined as a small area of EE localized within 1 to 2 cm.…”
Section: Methodsmentioning
confidence: 99%
“…The inflammatory and fibrostenotic scores were calculated ( 10 ). Regarding the location of endoscopic findings, the phenotype was divided into diffuse and localized EE in the previous study ( 11 ). The localized type was defined as a small area of EE localized within 1 to 2 cm.…”
Section: Methodsmentioning
confidence: 99%
“…There are some cases in which abnormal findings are localized to a small area at the lower end of the esophagus 31 . We found that the diagnostic ability was much lower in the localized type than in the diffuse type, and there was no diagnostic improvement with the addition of LCI (Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…EoE was histologically proven to have eosinophilic inflammation, with a peak of more than 15 eosinophils/high‐power field by obtaining more than two biopsy samples. EoE was classified into two subtypes: diffuse type and localized type according to the endoscopic phenotype with histological supporting findings as previously reported 31 Thus, the diffuse type was defined as a widespread area of eosinophilic inflammation involving one or more of three locations: upper, middle, and lower esophagus. Multiple biopsies were obtained from the esophagus for endoscopically suspected diffuse‐type EoE.…”
Section: Methodsmentioning
confidence: 93%
“…Several findings, such as multiple polypoid lesions [ 79 , 80 , 81 ], tug sign/pull sign [ 82 , 83 ], ankylosaurus back sign [ 84 ], and caterpillar sign [ 49 ] have been reported. In addition, endoscopic abnormalities have been localized in small areas of the lower end of the esophagus, or with patchy distribution in 30–40% of patients [ 85 , 86 ] ( Figure 8 ). Such localized types may be missed, unless the whole esophagus is carefully observed with proper expansion by both air inflation and deep inspiration during endoscopy.…”
Section: Other Endoscopic Findings Suggestive Of Eoementioning
confidence: 99%